The Chinese Concept of the Individual and the Reception of Foreign Law - Ma, Herbert H. P. (Columbia Journal of Asian Law, 1995)
The topic of this lecture is “The Chinese Concept of the Individual and the Reception of Foreign Law “‘ I have based my discussion of this topic on the following presumptions. First, “foreign law” referred to hereafter basically should be taken to mean modem Western law as found in democratic countries and based primarily upon the protection of the rights and freedoms of the individual, the concept of which was first highly developed in the seventeenth and eighteenth centuries. Second, I have assumed that China has had its own concept of the “individual” underlying its unique legal traditions, and that this concept is very different from that of the Western world. Third, this discussion is based on the assumption that while China turned to the West for the modernization of its laws around the turn of the twentieth century, the Chinese have not wholeheartedly adopted the Western concept of the individual, and as a result, have not been able to administer successfully their modern westernized laws. I shall try to avoid dwelling solely upon the concept of the individual, for the simple reason that there are, in the West and East, so many theories about the nature and the status of the individual. I shall only attempt to compare the concept of the individual underlying modern foreign and Chinese law with that upheld by traditional Chinese law I believe that such a comparison will reveal how poorly modern westernized Chinese law actually fares without a pertinent concept of the individual supporting it.